2018
DOI: 10.1111/jav.01474
|View full text |Cite
|
Sign up to set email alerts
|

A bridge between oceans: overland migration of marine birds in a wind energy corridor

Abstract: Located at the shortest overland route between the Gulf of Mexico and the Pacific Ocean, Mexico's Tehuantepec Isthmus is a globally important migratory corridor for many terrestrial bird species. The Pacific coast of the Isthmus also contains a significant wetland complex that supports large multi-species aggregations of nonbreeding waterbirds during the boreal winter. In recent years, extensive wind energy development has occurred in the plains bordering these wetlands, directly along the migratory flyway. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…All resighted individuals were ringed during previous northward migrations along the US Atlantic coast, most of them in the western Gulf of Mexico (Texas and Louisiana). Although the subspecies roselaari can also occur in certain parts of the rufa non‐breeding range (Carmona et al, ), the Gulf of Mexico is primarily used by C. c. rufa red knots to overwinter (McKellar et al, ; Newstead et al, ), and to a lesser extent during their northward migration to the Canadian Arctic (Lamb et al, ; Newstead et al, ). In addition, individuals overwintering at Chiloé have not been reported on the Pacific coast of North America, despite an important resighting effort on the western coasts of the USA and Canada (Bishop, Buchanan, McCaffery, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All resighted individuals were ringed during previous northward migrations along the US Atlantic coast, most of them in the western Gulf of Mexico (Texas and Louisiana). Although the subspecies roselaari can also occur in certain parts of the rufa non‐breeding range (Carmona et al, ), the Gulf of Mexico is primarily used by C. c. rufa red knots to overwinter (McKellar et al, ; Newstead et al, ), and to a lesser extent during their northward migration to the Canadian Arctic (Lamb et al, ; Newstead et al, ). In addition, individuals overwintering at Chiloé have not been reported on the Pacific coast of North America, despite an important resighting effort on the western coasts of the USA and Canada (Bishop, Buchanan, McCaffery, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alves, Dias, Méndez, Katrínardóttir, & Gunnarsson, ), red knots, assisted by tailwinds, may surpass their theoretical limit of endurance flight (c. 5,000 km; Hedenström, ), which would enable them to reach Texas or Louisiana. However, individuals with alternative migration strategies (Piersma et al, ), or those encountering bad weather conditions en route (Shamoun‐Baranes et al, ), may use other suitable staging, stopover or even emergency areas where the species has been reported; for example, Oaxaca, Mexico (Binford, ; Lamb et al, ), Delta del Estero Real, shared by Nicaragua and Honduras (J.G. Navedo, personal observations) and Panama bay (R. Miró, personal communication, November 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Land and mountain ranges may not represent a barrier for the migration of experienced seabirds: geolocator-tagged Arctic Terns Sterna paradisaea from an Alaskan colony travelled from the Pacific to the South Atlantic Ocean across the southern Andes of South America (Duffy et al 2013). A regular overland migration route for marine birds from the Gulf of Mexico to the Pacific has recently been identified (Lamb et al 2018) and there is long-standing evidence for the trans-Pennine migration of Common Terns Sterna hirundo and Sandwich Terns Thalasseus sandvicensis across the United Kingdom (UK) from the North Sea to the Irish Sea in autumn (Ward 2000, Wernham 2002. Furthermore, Long-tailed Skuas Stercorarius longicaudus may migrate across the UK in spring (Wynn et al 2014).…”
mentioning
confidence: 99%
“…Furthermore, Long-tailed Skuas Stercorarius longicaudus may migrate across the UK in spring (Wynn et al 2014). While taking a direct overland route between different marine resources may be an easy strategy for a seabird, man-made obstacles such as wind farms represent unnatural hazards with potentially unexpected conservation implications which need to be recognized (Lamb et al 2018). Therefore, it is important to identify the routes and extent of overland movements as components of the migration strategies of seabirds.…”
mentioning
confidence: 99%
“…For example, most of the samples from Louisiana were collected from a small colony on an island, which did not have documented nesting Reddish Egrets until recently (Selman & Davis, 2015). Therefore, the unique genetic deme in Louisiana, which also included some individuals from Florida (Figure 1d) (Geary et al, 2015;Koczur et al, 2018;Lamb et al, 2017), we found little evidence to support that immigrants breed at high frequencies with TA B L E 3 Analysis of Molecular Variation (AMOVA) tests for four different management unit (MU) models ( Figure 1a) Regarding dispersal, Geary et al (2015) found only one female out of four dispersed greater than 120 km from their natal colony, whereas 13 out of 21 males dispersed greater than 120 km.…”
Section: Discussionmentioning
confidence: 99%